Early neutrophil activation and NETs release in the pristane-induced lupus mice model. - Solange Carrasco; Bernadete L Liphaus; Tatiana Vasconcelos Peixoto; Thais Martins Lima; Sueli Kunimi Kubo Ariga; Zelita Aparecida Jesus Queiroz; Thays de Matos Lobo; Sergio Catanozi; Letícia Gomes Rodrigues; Antônio Santos Filho; Walcy Rosolia Teodoro; Ana Paula Pereira Velosa; et al. (PLoS ONE)
Background NETosis is recognized as an important source of autoantigens. Therefore, we hypothesized whether the pristane-induced lupus mice model shows early activation of neutrophils, the presence of low-density granulocytes (LDGs), and neutrophil extracellular traps (NETs) release, which could contribute to the development of a lupus phenotype. Methods Twelve female wild-type Balb/c mice were intraperitoneally injected with pristane (n = 6; pristane group) or saline (n = 6; control group). Five days after the injection, blood, peritoneal lavage, bone marrow, and spleen samples were collected for flow cytometry analyses of activated neutrophils (Ly6G+CD11b+), LDGs (CD15+CD14low), and NETs release (Sytox Green+). Results The pristane-induced mice group had a significantly increased number of blood activated neutrophils and LDGs as well as NETs released by these cells compared to the saline-injected control group and the basal values determined 12 days before the injection. The pristane group also had a significantly increased number of activated neutrophils, LDGs, and NETs released compared to the control group for the peritoneal lavage and bone marrow, except total cell count in spleen. Conclusions We demonstrated early changes in the innate immune response such as an increased number of activated neutrophils and LDGs and mainly increased NETosis in the pristane-induced mice model which may be considered as the primary event triggering lupus development.